Penerapan Model Pembelajaran Index Card Match Untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Ilmu Pengetahuan Sosial Kelas V - Maryam M, St; Shasliani, Shasliani; Amalia, Reski (Universitas Negeri Makassar, 2024)
This research is classroom action research (PTK) which aims to find out the process of implementing the Index Card Match learning model to improve the learning process and improve student learning outcomes in social science learning in class V UPT SD Negeri 178 Pinrang. The approach used in this study is a qualitative approach. The data collection techniques used in this research are observation, tests and documentation. The subjects of this research were the class teacher and students, totaling 16 students. The research was carried out in two cycles. In cycle I, the research results on the learning process were at sufficient qualifications (C) and the results of the learning tests were at sufficient qualifications (C). Cycle II research results on the learning process were in good qualifications (B) and learning test results were in good qualifications (B). The conclusion of this research is that the application of the Index Card Match learning model can improve the learning process and outcomes of social science students in class V UPT SD Negeri 178 Pinrang.